Changes in Regional Homogeneity of Medication-Free Major Depressive Disorder Patients With Different Onset Ages - Zhang, Zijian; Chen, Yayun; Wei, Wei; Yang, Xiao; Meng, Yajing; Yu, Hua; Guo, Wanjun; Wang, Qiang; Deng, Wei; Li, Tao; Ma, Xiaohong (Frontiers in Psychiatry, 2021)
Background: Neurobiological mechanisms underlying the development of major depressive disorder (MDD) may differ depending on onset-ages. Our aim was to determine whether regional homogeneity (ReHo) changes in early-onset depression (EOD) and late-onset depression (LOD) are different, which could also delineate EOD and LOD. Methods: 91 MDD patients and 115 healthy controls (HCs) were recruited, and collected resting-state functional magnetic resonance imaging data. The ReHo comparison was conducted using analysis of variance. Results: Compared with HCs, MDD patients showed decreased ReHo in the left precentral gyrus and the left middle cingulum area, and increased ReHo in the left middle orbital frontal gyrus, Superior Temporal Gyrus. Compared with LOD patients and young HC, EOD patients had significantly increased ReHo in the right inferior frontal triangular gyrus and the left postcentral gyrus. However, compared with young HC, EOD patients showed decreased ReHo in the right superior frontal gyrus/supplementary motor area and the right medial frontal gyrus. ReHo in right inferior frontal triangular gyrus was negatively correlated with the severity of cognitive disturbance in LOD patients (r = -0.47, p = 0.002), but not in EOD patients (r = 0.21, p = 0.178). Conclusion: MDD patients with different onset-ages may have different pathophysiological mechanisms, the EOD patients existed more abnormal regional homogeneity than LOD patients in prefrontal lobe, especially the right inferior frontal triangular gyrus.